Rebelious Women: Indigenous Guerrilla in Guatemala (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
Rural women belonging to different organizations joint in 2006 to meet and discuss. That was the first time the ex guerrilla women expressed their desire to be recognized as such. By being part of Red de Mujeres de Plataforma Agraria, which joins women from peasant organizations, this desire became a demand: recognition through written word. The research team visited Kumool, the organization from which these women take part, in 2007 and they were sure about wanting a book about their experiences as com- batants, about living in the highland jungle, which made them what they are today. The result was more than just a testimonial compendium, which took many discussion time. We organized their stories in three blocks: the body, the feelings and the current situation.The present article com- prises what the stories tell about these three topics, along with some reflections about memory, which are the result of participating in the process of listening the narrations in Guatemala’s sociohistory.
Keywords: Guerrilla; Indigenous Women; Memory; Genocide.